Numerical modelling of light propagation in surface plasmon resonance sensor with liquid crystal - Yarmoshchuk, Ye.S.; Zadorozhnii, V.I.; Reshetnyak, V.Yu. (Condensed Matter Physics, 2018)
The five-layer nanorod-mediated surface plasmon sensor with inhomogeneous liquid crystal layer was theoretically investigated. The reflectance as the function of the incident angle was calculated at different voltages
applied to the liquid crystal (LC) for different analyte refractive indices. By changing the LC director orientation
one can control the position of the reflective dips and choose the one that is the most sensitive to the analyte
refractive index. At the chosen angle of incidence, the analyte refractive index can be found from the reflectance
value. The director reorientation effect is stronger when the prism refractive index is between ordinary and extraordinary refractive indices of the LC. In this case, the voltage increase and the prism refractive index decrease
have a similar effect on the reflectance features. Теоретично дослiджено п’ятишаровий плазмонний сенсор з шаром наночастинок та неоднорiдним шаром рiдкого кристалу. Розраховано коефiцiєнт вiдбивання як функцiю кута падiння при рiзних значеннях
показника заломлення аналiту та прикладеної до рiдкого кристалу (РК) напруги. Змiнюючи орiєнтацiю директора рiдкого кристалу, можна контролювати положення мiнiмумiв кривих вiдбивання i вибрати той,
що найбiльш чутливий до показника заломлення аналiту. При вибраному кутi падiння показник заломлення аналiту може бути визначений по значенню коефiцiєнта вiдбивання. Вплив переорiєнтацiї директора
сильнiший, коли значення показника заломлення призми є мiж звичайним i незвичайним показниками
заломлення РК, в цьому випадку збiльшення напруги i зменшення показника заломлення призми мають
подiбний вплив на форму кривої вiдбивання.